Osteosclerosis in the extinct Cayaoa Bruneti (Aves, anseriformes) : insights on behavior and fligftlessness - Mendoza, Ricardo de (2015)
Fil: Mendoza, Ricardo de. División Paleontología Vertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata